Die Strafbarkeit des Betreibers professionell moderierter Online-Datingportale nach § 263 StGB - Fülscher, Friedrich Sebastian (Tectum Verlag, 2023)
Online dating between disappointed hopes and criminality: Based on actual cases in northern Germany, Friedrich Fülscher takes on the task of examining professionally moderated fee-based dating and chat sites for their relevance under criminal law, in particular fraud pursuant to § 263 StGB (German Criminal Code). The analysis and subsumption of the objective and subjective elements of the offence in the light of supreme court case law reveal serious substantive challenges that generally lead to a denial of criminal liability for fraud. Among other things, the author shows that clarification processes in general terms and conditions under civil law have an exclusionary effect.